Facile CO2 Separation in Composite Membranes. Issue 1 (3rd December 2018) - Saqib, Sidra; Rafiq, Sikander; Chawla, Muhammad; Saeed, Muhammad; Muhammad, Nawshad; Khurram, Shahzad; Majeed, Khaliq; Khan, Asim Laeeq; Ghauri, Moinuddin; Jamil, Farrukh; Aslam, Muhammad
Abstract: CO2 emission from anthropogenic sources has raised worldwide environmental concerns and hence proficient energy paradigm has tilted towards CO2 capture. Membrane technology is one of the efficient technologies for CO2 separation since it is environmentally friendly, inexpensive, and offers high surface areas. Various approaches are discussed to improve membrane performance focusing mainly on permeability and selectivity parameters. Different types of fillers are incorporated to reach the Robeson's upper bound curve. In this review, polymer‐inorganic nanocomposite membranes for the separation of CO2, CH4, and N2 from various gas mixtures are comprehensively discussed. Metal organic frameworks (MOFs) and ionic liquid (ILs) mixed‐matrix membranes are also considered. Abstract : Membrane technology is considered as an efficient, environmentally friendly, and inexpensive technology for CO2 separation. Various approaches to improve membrane performance are reviewed with the focus on permeability and selectivity parameters. Polymer‐inorganic nanocomposite membranes, metal organic frameworks, and ionic liquid mixed‐matrix membranes are also discussed and evaluated.